La unificación nacional que dejó una nación dividida: el gobierno del Presidente Zelaya y la "reincorporación" de la Mosquitia a Nicaragua en 1894 - Wünderich, Volker (1996)
An analysis of the motivations and political conduct of the Liberal government headed by President José Santos Zelaya, during the early stage of reincorporation of Mosquitia to Nicaragua. The prevailing concepts with respect to territory, sovereignty, and material progress did not take into account the legitimate rights of the coastal inhabitants.